Changes in serum urate and urate excretion with age - Stiburkova, Blanka; Bleyer, Anthony J (Advances in chronic kidney disease, 2012)
A cross-sectional study was performed evaluating serum urate levels and fractional excretion of urate in a group of patients referred for screening for inherited metabolic disorders. From 2003 through 2010, serum urate, serum creatinine, urinary urate, and urinary creatinine levels were obtained as part of a research protocol to identify individuals with inherited metabolic disorders. These values were compared with individuals with uromodulin-associated kidney disease (UAKD). Laboratory studies were evaluated on 1274 individuals. The fractional excretion of urate was very high in infancy (27 ± 21% in males and 29 ± 25% in females). The high fractional excretion declined rapidly over the first several months of life, together with a decline in serum urate levels. The mean fractional excretion was approximately 8% during childhood. It then remained stable in females but decreased in males to 5.9 ± 5.6% in adolescence and 5.3 ± 3.8% in adulthood. Serum urate levels in childhood were influenced by age and kidney function but not gender. In adulthood, serum urate was influenced by age, gender, and estimated glomerular filtration rate. Although patients with UAKD had lower fractional excretions of urate than individuals with normal kidney function, there was considerable overlap.
Keywords: Young Adult; Cross-Sectional Studies; Kidney Diseases; Male; kyselina močová; Child, Preschool; mladý dospělý; Adolescent; uromodulin; Infant; Child; Uromodulin; dítě; Adult; Age Factors; Kidney; dospělí; nemoci ledvin; mužské pohlaví; Uric Acid; mladiství; Kidney Function Tests; předškolní dítě; lidé; ženské pohlaví; Humans; ledviny; kojenec; věkové faktory; průřezové studie; vyšetření funkce ledvin; Female; lidé středního věku; Middle Aged